Museum visitor preference for the physical properties of 3D printed replicas - Wilson, P; Stott, J; Warnett, J; Attridge, A; Smith, M; Williams, M (Elsevier, 2018)
Within museology, the past few decades have seen a resurgence in focus on the experience of the museum visitor and what museum professionals can do to provide more meaningful, memorable visits. One method of achieving this is through multisensory experiences, encouraging museum visitors to use a range of senses to explore an exhibition, a process known to facilitate the generation of memorable experiences. However, as many museum objects are fragile and potentially irreplaceable, surrogates must be created in order to encourage such interaction within exhibitions. Use of 3D printed replicas is one approach, creating risk-free accurate copies of rare objects for visitors to handle. Despite the popularity of this technique, little user experience research has been carried out investigating the perspective of visitors and as a result, little guidance on best practices exist at this stage. Here, we present an investigation into visitor preference of the physical properties of 3D printed replicas, using semantic differentials, exploratory factor analysis and other statistical approaches. The study finds that the most important aspect of 3D prints for museums visitors was that of verisimilitude, visitors dominantly preferring prints that best represented the original specimen, with factors including the robustness of a 3D printed replica and its quality being important to museum visitors, although the importance of these to visitor preference varied. Also discussed are a number of further questions of key interest to heritage workers, including the perspective of the varied nature of museums audience, blind and partially-sighted visitors and their impact on learning experiences.